The Demographic Dividend As A Pathway To Development: The Role of Fertility and Education in Sub-Saharan Africa. A Narrative Review - Osei-Appaw, Akosua; Christian, Aaron (International Journal of Economics, 2022)
Purpose: Sub-Saharan African countries are experiencing rapid population growth. This is essential in achieving the Demographic Dividend. Age structure, fertility and education play a key role in the achievement of the Demographic Dividend. Although gains from age structure are crucial, its gains are not automatic. However, the inter-relatedness of fertility and education makes a reduction in fertility a cause and effect on investments in education. Methodology: This narrative review looks at studies discussing the Demographic Dividend from a development theory point of view. It is an attempt to explain how different countries within Sub-Saharan Africa are faring due to the inter-play between fertility and education. Findings: The results highlight how the Demographic Dividend is really an Educational Dividend. It also shows a negative correlation between education and fertility across regions and time. The political environment with emphasis on good governance plays a key role in harnessing the Demographic Dividend. Aside this, a fertility decline alone could worsen the existing economic conditions if it is not in tandem with higher education rates among young adults. This is in line with Ester Boserup's view of seeing population as a resource. Unique contribution to theory, practice and policy (recommendation): A conducive political environment attracts investments and creates room for entrepreneurship and job creation which are necessary to be able to harness the Demographic Dividend. There's the need to however, look at the definition of working age group and conditions necessary to promote entrepreneurship.